(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABTRACK : This study aims to determine the effectiveness of using the Academic Portal at Sam Ratulangi University, especially the Faculty of Social and Political Sciences. This research was conducted using qualitative descriptive method. The results showed that: Use of Academic Portal Fispol Sam Ratulangi University in Manado was very helpful during the process of learning but not fully effective. Entry portal provides benefits to the academic institutions, students, lecturers and managers to be able to present all the needs, such as: Card Planing Study, Lecture Attendance List, Card Study Results, academic transcripts, as well as matters relating to the management of Graduation and diploma and other data needs. Use of Academic Portal in Fispol Unsrat not been effective in terms of time and costs and yet provide satisfaction for all users; Factors Supporting Use of Academic Portal Fispol Sam Ratulangi University in Manado are all elements of the campus, namely: leadership, staff and students as well as quality assurance. In addition, the central and provincial government support and human resources employees very major contribution in academic portal usage; The obstacles encountered in the use of Academic Portal Fispol Sam Ratulangi University in Manado is internal constraints and external constraints. Internal constraints are constraints that come from the users in this case are the students and lecturers as well as the manager himself who often lack discipline in terms of time to access the portal, causing entered data can not be registered because it delays access and input data online. External constraints are the constraints that come from outside which in this case is a disorder of the Internet network; and efforts are being made to overcome the obstacles encountered in the use of the portal academic Fispol Sam Ratulangi University in Manado not all be implemented must be through socialization and introduction to the faculty and students back, also in the form of an announcement on the bulletin boards of faculty regarding the charging time and the deadline for filling the portal academic , but it also attempted dissemination through seminars to introduce more features and for the smooth process of the lecture. Besides maximizing the existing infrastructure to support the operation of the academic portal usage such as efforts to overcome problems with the procurement network of free internet network in a campus environment and other measures which have not been done. Keywords: Effectiveness, Academic Portal